w/-3=-6

Simple and best practice solution for w/-3=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for w/-3=-6 equation:


w in (-oo:+oo)

w/(-3) = -6 // + 6

w/(-3)+6 = 0

6-1/3*w = 0 // - 6

-1/3*w = -6 // : -1/3

w = -6/(-1/3)

w = 18

w = 18

See similar equations:

| k-2/5=-67/55 | | d-4=-10 | | 64x^5-64x^3=x^2-1 | | d+10=15 | | 3+a=-5 | | -1/6d=-1/27 | | 64x^5=x^2 | | 18=t+6 | | m/3=6 | | d+1=9 | | t-1/2=23/2 | | b-2=-6 | | a-3/4=-1 | | -8+a=-2 | | -9/4=x-3 | | m/5=-5/6 | | -1/2+w=23/2 | | -1+n=0 | | n/7=5 | | -3/10+t=87/10 | | -1+k=-14/9 | | a+10=15 | | d=3/5 | | d+8=9 | | w+3=-8 | | b+8=65/9 | | a/7=-1/3 | | n-1=8 | | 1/2w=3/20 | | w-7=0 | | d-5=-46/11 | | k-2=-4/3 |

Equations solver categories